Prevalence of Workforce Diversity Research Among Surgical Specialties in the United States: How Does Plastic Surgery Compare?. Issue 6 (December 2021) - Reghunathan, Meera; Blum, Jessica; Gosman, Amanda A.; Butler, Paris D.; Chen, Wendy
Abstract : Background: Plastic surgeons are not as diverse as expected in relation to the increasingly diverse patient and medical student population. The authors assess the state of diversity in 8 primary surgical specialties in the United States and evaluate trends in research interest in diversity over the past 30 years. Methods: Articles regarding diversity in surgery from 1990 to 2020 were systematically reviewed. The Association of American Medical Colleges Physician Specialty Data Reports and the Accreditation Council for Graduate Medical Education Data Resource Books provided resident/fellow and faculty data from 2011 to 2016. Trends were analyzed over time per specialty. Results: From 1990 to 2020, a total of 199 publications related to diversity were identified among the various surgical specialties. Orthopedic surgery had significantly more publications per year compared with other specialties ( P < 0.05). Every specialty demonstrated a significant increase in publications about diversity over time ( P < 0.05). A majority of publications were related to sex rather than underrepresented in medicine topics. The proportion of female surgeons was significantly higher for plastic surgery than for orthopedic surgery and neurosurgery ( P < 0.001). Plastic surgery exhibited the highest growth rate in female residents (+1.6% per year, P < 0.001). The proportion of underrepresented minorities composing surgical trainees has not significantly increased in any surgical specialty between 2011 and 2016 ( P > 0.05). Conclusions: Although diversity representation in surgery has somewhat improved, the rate is too slow to match the growing diversity of the US population. Outcomes have been disparate between specialties and demonstrate greater increases in sex equality relative to ethnic/racial equality. Evidence-based interventions need to be developed and implemented.